Personel Wanita Dalam Industri Pembinaan: Bentuk Dan Kesan Gangguan Seksual Dari Aspek Fizikal, Mental Dan Psikologi - Ahmad Latiffi, Aryani; Mat Nawi, Siti Syakirah; Bilal, Kamalludin (Research in Management of Technology and Business, 2020)
Women have become a very important source of energy in the construction industry. Nowadays, women have wide opportunities to hold various positions in the job market. However, it also exposes female workers to the risk of sexual harassment in the workplace. The objectives of this study are to identify the forms of sexual harassment committed against female personnel and to examine the effects of sexual harassment on female personnel in terms of physical, mental, and psychological. This study focuses on female personnel working in G7 contractor companies in Kota Bharu, Kelantan. Data were obtained from project managers, project engineers, quantity surveyors, site managers, site engineers and project executives using a set of questionnaires form. The number of respondents involved is 40 people. Data gained from the respondents were analyzed using software of Statiscal Package For The Social Science (SPSS). The analysis of the study shows that forms of sexual harassment occur in terms of verbal, visual, physical and psychological. It was found that the respondents have a high level of awareness about the forms of sexual harassment in term of verbal, gestures, psychological and physical. Meanwhile, the effects of sexual harassment covering three parts namely physical, mental and psychology. An example of a physical aspect is decreased work performance. Examples for mental aspect and psychology are experienced trauma and emotional as well as not enthusiastic. This study provides knowledge to women to always be vigilant and emphasize the safety and health aspects while at work so as not to fall victim to sexual harassment.